Color Hierarchy as a Visual Preservation Strategy in the Adaptive Reuse of Joglo Architecture: A Color Mapping and Semiotic Approach - Citra Fakhira Atsir; Yulianto P. Prihatmaji; Army Wiratama (Universitas Bandar Lampung (UBL), 2026)
This study examines color as a culturally meaningful visual system in the adaptive reuse of traditional Joglo architecture. Focusing on five Joglo buildings with varied functions and ownership backgrounds, the research explores color mapping as a strategy of visual preservation. Using a qualitative interpretative approach—combining observation, visual documentation, and interviews—the analysis integrates color mapping theory, color semiotics, and psychological perspectives. The findings reveal a consistent color hierarchy, with darker tones on roofs and structures, transitional tones on walls, and lighter neutral floors, persisting across functional changes and demonstrating the stable visual logic that supports cultural continuity in Joglo architecture.